Investigation of Flooding Hydrological Behavior in Razavar Watershed Using Statistical Analysis, SCS Model and Profile of the River - Amjad Maleki; Homayon Hasadi; Nooshin Pirouzinejad (جغرافیا و توسعه, 2014)
Razavar watershed on the north of Kermanshah province is one of the flooding basins that causes flooding in watery years. For investigating watershed flooding, the statistical  analysis of real data of the area, SCS model and surveying river cross section have been used. by dividing watershed to hydrologic homogeneous units and study ,  the factors influencing on flood such as vegetation cover, land use, time of concentration, lag time , slop ,geology ,pedology ,rainfall intensity were studied .finally CN and S map are provided and    runoff height and peak discharge has been estimated by using SCS in smada software. The important factor in this software is the coefficient of flood recession curve. This coefficient indicates the  hydrological  behavior and morphological condition of the river at flood time. To obtain this coefficient, the flood hydrograph of pirmazd station has been plotted and interpreted. Analysis of the real flood hydrograph shows that the recession time of flood in Razavar watershed is 5 times of flood rising, and this represent the hydrological behavior of river which cant discharge the flood from the basin at the flood time. To identify the river hydrological status, surveying river profile was performed. The results showed that  expect the  river profile at pirmazd station,  no other  sections is able to pass  peak discharge with 5years of return periods and even the river profile at Mehregan station cannot discharge flood of 2years return period and the cause of basin flooding  is the narrow channel from upstream toward downstream which causes flood every year.